(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The conventional textile industry, particularly the water- and resource-intensive production of terry fabrics, faces immense pressure to transition towards circular and sustainable models. The incorporation of recycled fibers and rapidly renewable alternatives into high-consumption products like towels represents a significant opportunity for reducing environmental impact. This research aimed to critically assess the technical feasibility and performance of using blended yarns from post-industrial recycled cotton and bamboo viscose as pile materials in terry fabric, providing a direct comparison to conventional virgin cotton across key functional properties. Three terry fabric samples were manufactured on a controlled loom setting with an identical 3-pick structure and pile height. The sole variable was the pile warp yarn: 1) 100% virgin cotton (control), 2) 50/50 recycled cotton/virgin cotton, and 3) 50/50 bamboo viscose/virgin cotton. The fabrics underwent rigorous testing for water absorption capacity and rate (AATCC 79), fabric softness (Handle-O-Meter, ASTM D6828), bursting strength (ASTM D3786), and abrasion resistance (ASTM D4966). The bamboo viscose blend demonstrated exceptional performance in comfort-oriented properties, exhibiting a 40% higher water absorption capacity and a 15% improvement in softness (lower bending length) compared to the virgin cotton control. In contrast, the recycled cotton blend showed water absorption comparable to the control but suffered a significant 20% reduction in both bursting strength and abrasion resistance. The bamboo blend’s mechanical durability was intermediate, slightly lower than virgin cotton but substantially better than the recycled blend. Bamboo viscose is identified as a superior sustainable alternative for terry pile yarn, offering enhanced absorbency and a luxurious soft hand, making it ideal for premium products. Recycled cotton presents a viable pathway for reducing virgin material use but necessitates application in less demanding products due to its compromised durability. This study provides a scientific basis for material selection in the sustainable design of terry textiles.